Comparison of gene disruption induced by cytosine base editing‐mediated iSTOP with CRISPR/Cas9‐mediated frameshift. (29th April 2020) - Dang, Lu; Li, Guanglei; Wang, Xinjie; Huang, Shisheng; Zhang, Yu; Miao, Yuanxin; Zeng, Lisi; Cui, Shuzhong; Huang, Xingxu
Abstract: Objectives: Recently developed CRISPR‐dependent cytosine base editor (CBE), converting four codons (CAA, CAG, CGA and TGG) into stop codons without DNA double‐strand breaks (DSB), serves as an efficient gene disruption strategy besides uncontrollable CRISPR‐mediated frameshift. However, the detailed difference of gene knockout between the two systems has not been clarified. Materials and methods: Here, we selected some sgRNAs with different position background, then HEK293T cells were transfected with CBE/Cas9 plasmids together with sgRNAs. GFP‐positive cells were harvested by fluorescence‐activated cell sorting (FACS) 48 hours after transfection. Genomic DNA was collected for deep sequencing to analyse editing efficiency and genotype. RNA and protein were extracted to analyse gene mRNA level using qPCR analysis and Western blot. Results: Here, we compared the gene disruption by CBE‐mediated iSTOP with CRISPR/Cas9‐mediated frameshift. We found BE‐mediated gene knockout yielded fewer genotypes. BE‐mediated gene editing precisely achieved silencing of two neighbouring genes, while CRISPR/Cas9 may delete the large fragment between two target sites. All of three stop codons could efficiently disrupt the target genes. It is worth notifying, Cas9‐mediated gene knockout showed a more impact on neighbouring genes mRNA level than the BE editor. Conclusions: Our results reveal the differences between the two gene knockout strategies and provide useful information for choosing the appropriate gene disruption strategy.